An interpretive investigation of trust and workflow in advertising communities - Chim, Jimmy Chi Lung (2016)
Adopting a socio–economic perspective and a multimethod field research approach this thesis investigates the correlation between trust and workflow in advertising communities of practice. Using a semiotic mode of analysis a comparative examination of offline and online communities will be conducted to inspect the practices of trust when multiple stakeholders follow the creative workflow process to fulfil creative briefs. The motivation to lead the research stems from a current lack of understanding of how trust is operationalized in online creative communities. Shortcomings from the literature 1) do not account for the significance of constructed workplace settings in the offline domain, 2) focus on providing generalisations through quantification, while fail to offer insights through qualitative methods and 3) overlook the weaknesses of trust in professional relationships.